EL CARIOTIPO FUNDAMENTAL EN TRAUBIA MODESTA (PHIL.) RAVENNA (AMARYLLIDACEAE) - Baeza, Carlos M.; Novoa, Patricio; Ruiz, Eduardo; Negritto, María A. (Gayana Botánica, 2009)
The karyotype of Traubia modesta (Phil.) Ravenna was examined. The species has 2n = 2x = 16 chromosomes, with 4m + 12st chromosomes. Traubia presents a very different karyotype in comparison to other genera of Amaryllidaceae from Chile.